2018
DOI: 10.1103/physreve.98.033310
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase parametrization and solidification in many-body dissipative particle dynamics

Abstract: Many-body dissipative particle dynamics (MDPD) is a mesoscale method capable of reproducing liquid-vapour coexistence in a single simulation. Despite having been introduced more than a decade ago, this method remains broadly unexplored and, as a result, relatively unused for modelling of industrially important soft matter systems. In this work, we systematically investigate the structure and properties of an MDPD fluid. We show that, besides the liquid phase, the MDPD potential can also yield a gas phase and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As a result of coarse-graining from MD, the critical time step required in DPD models is several orders of magnitude larger than their MD counterparts, thus permitting sampling of both length and time scales equivalent to those experimentally measurable. In DPD, simulations of multiphase fluid dynamics (including fluid–fluid and fluid–solid interactions) are made possible by several multiphase-enabled DPD models. Among the DPD model variants, the many-body DPD (mDPD) model is a prominent candidate for mesoscopic simulations of fluid flow in nanoporous materials. The mDPD model can reproduce the compressibility of real liquid fluids as a function of pressure by considering the many-body interactions , and has been applied for qualitative studies of surface tension, contact angle characterization, , multiphase flow in microchannels, droplets impact on surfaces, and nanocapillaries . A recent review of mDPD on its theories and applications is reported in Zhao et al…”
Section: Introductionmentioning
confidence: 99%
“…As a result of coarse-graining from MD, the critical time step required in DPD models is several orders of magnitude larger than their MD counterparts, thus permitting sampling of both length and time scales equivalent to those experimentally measurable. In DPD, simulations of multiphase fluid dynamics (including fluid–fluid and fluid–solid interactions) are made possible by several multiphase-enabled DPD models. Among the DPD model variants, the many-body DPD (mDPD) model is a prominent candidate for mesoscopic simulations of fluid flow in nanoporous materials. The mDPD model can reproduce the compressibility of real liquid fluids as a function of pressure by considering the many-body interactions , and has been applied for qualitative studies of surface tension, contact angle characterization, , multiphase flow in microchannels, droplets impact on surfaces, and nanocapillaries . A recent review of mDPD on its theories and applications is reported in Zhao et al…”
Section: Introductionmentioning
confidence: 99%
“…In our modeling, attractive patch–patch interactions are required to compete with the (screened) repulsive interactions between the particles. Moreover, the importance of many-body interactions in the prediction of the solid–liquid phase behavior and clustering of charged colloidal particles is given addressed to by several authors. …”
Section: Introductionmentioning
confidence: 99%
“…In our recent work 20 we determined the regions of the phase diagram of an MDPD fluid that give rise to the liquid phase. Based on the measurements of liquid density and surface tension as a function of the interaction parameters Ã, B and fixing rd , for example at 0.75, we solved for the interaction parameters from the material properties, in this case compressibility and surface tension.…”
Section: B Parameterisation For Real Liquidsmentioning
confidence: 99%
“…6a show a satisfactory albeit not perfect agreement, only apart from N m = 1 and 2, where the deviation is more significant. At these low CG degrees, the densities are very high and already out of the range of validity of the density fit, 20 resulting in incorrect liquid behaviour. Increasing the many-body cutoff to rd = 0.85, Fig.…”
Section: Surface Tensionmentioning
confidence: 99%